Theory and method in historical ethnomusicology - McCollum, Jonathan; Hebert, David G. (Lanham, Maryland : Lexington Books, 2014)
Theory and Method in Historical Ethnomusicology demonstrates various ways that new approaches to historiography--and the related application of new technologies--impact the work of ethnomusicologists who seek to meaningfully represent music traditions across barriers of both time and space.
Foundations of historical ethnomusicology / Jonathan McCollum and David G. Hebert -- Methodologies for historical ethnomusicology in the twenty-first century / David G. Hebert and Jonathan McCollum -- Philosophy of history and theory in historical ethnomusicology / David G. Hebert and Jonathan McCollum -- Hearing echoes, sensing history : the challenges of musical diaspora / Judah Cohen -- Ancient music, modern myth : Persian music and the pursuit of methodology in historical ethnomusicology / Ann Lucas -- Analysis of notation in music historiography : Armenian neumatic khaz from the ninth through early twentieth centuries / Jonathan McCollum -- Southern American fiddling through the mid-nineteenth century : three snapshots with modern connections / Chris Goertzen -- A tale of two sensibilities : Hindustani music and its histories / Daniel M. Neuman -- The legacy of music archives in historical ethnomusicology : a model for engaged ethnomusicology / Diane Thram -- Contested contextualization : the historical construction of East Asian music / Keith Howard -- Advancing historical ethnomusicology / Jonathan McCollum and David G. Hebert.
Includes bibliographical references and index.
Print version record.
Keywords: Historical ethnomusicology; Music -- Historiography; MUSIC -- Genres & Styles -- Classical; MUSIC -- Reference; Historical ethnomusicology; Music -- Historiography; Ethnomusicologie; Musique -- Historiographie; Electronic books